Red de sensores para el análisis de vibración en puentes utilizando acelerómetros triaxiales - Vargas-Ruiz, Omar Fernando (Instituto Tecnológico de Costa Rica, 2018)
In the evaluation of the state of the bridges in our country, one of the tests applied is the vibration analysis procedure, in which it is possible to observe the dynamic behavior of the structure and to take the corresponding measures of maintenance against any damage or failure that may be present in the structure. The e-Bridge project of the School of Engineering in Construction of the Technological Institute of Costa Rica, since 2011 has focused on finding solutions that allow the studies of bridge-type structures with an integrated system in which all the process of analysis of the different physical variables that affect a structure is performed reliably and with measurement systems implemented within the same project. The present project shows the implementation of a network of sensors, using triaxial accelerometers, to know the behavior in the three dimensions of the structures. The communication is made through the star type topology, where there are three auxiliary measurement units and a central processing node for the subsequent storage of the information. The data coming from the secondary nodes are stored in a file on the SD memory card of the microcontroller, for further analysis of vibration in bridge structures. For the verification of the system at the level of laboratory tests, a metallic beam of 6 m in length is used and the results obtained are compared with a commercial professional vibration equipment. The error obtained was 38,31%.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018
Keywords: Acelerómetros; Puentes; Redes; Sensores; Vibración; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics